Leader Affective Presence and Feedback in Teams - Madrid, Hector P. (Frontiers in Psychology, 2020)
Affective Presence refers to the consistent and stable feelings that an individual tends to leave in their interaction partners. Expanding previous research on the application of affective presence to individuals in the role of leaders in teams, in this study, I examine whether leaders’ feedback behavior is related to the emergence of their affective presence. Using a multisource survey design with a sample of employees from a technology organization, as expected, results indicated that leader feedback behavior directed to the characteristics that team members should ideally have to perform well (ought self feedback) is positively related to leaders’ positive affective presence. In contrast, feedback directed to compare team members’ performance with other team members’ performance (normative cues feedback) is positively associated with leaders’ negative affective presence. As such, the study contributes to having an understanding of the etiology of affective presence in the context of teams, also informing organizational practitioners about how to manage leader influences on team members.